Dysmenorrhea on Mental Health, Quality of Life, and Its Factors among Women in Different Countries: A Literature Review - Carissa Aulia Ramadhani Sutopo; Ardian, Laurentius Johan (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background. Dysmenorrhea for many women is a burden in their lives. The high prevalence of dysmenorrhea among adolescents often receives less attention from the medical world because many consider that this dysmenorrhea is a normal thing even though doing activities during menstrual pain that comes every month makes women affected by dysmenorrhea feel disadvantaged because they cannot carry out their activities properly as usual. Taking time off is an option that helps relieve women who suffer from dysmenorrhea so that they can rest. In addition, sufferers usually do hot compresses and aromatherapy to relieve the pain. However, dysmenorrhea itself has not been confirmed so the treatment is still being developed today. Method. The journals were used by selecting a topic, then determining keywords to search for journals in English and conducting searches using several websites such as Google Scholar, Elsevier, and Taylor and Francis. Discussion. Considering that the prevalence of dysmenorrhea is quite high, it is really affecting a good percentage of young females, university students, through their regular academic, social, and psychological activities. Several underlying factors are there that determine its intensity, including hormonal imbalance, psychologic issues, endometriosis and adenomyosis, female genital mutilation, etc., cultural, and religious practices aggravating the intensity of menstrual pain. Yet, despite its impact, access to healthcare for many women is impeded by either financial constraints, lack of awareness, or societal normalization of pain, as was shown in Korea, where the utilization of healthcare for dysmenorrhea is poor. Further, the condition has several long-term implications, including possible implications for brain health and heightened levels of stress associated with premenstrual syndrome. Effective treatments include Dienogest and uterine artery embolization, which have relieved symptoms and improved quality of life, thus indicating the need for greater awareness, better access to care, and comprehensive management strategies. Conclusion. Dysmenorrhea is a disease that affects physically and mentally because it is usually caused by the menstrual period in every woman. Therefore, it is necessary to provide physical and mental treatment due to dysmenorrhea.